2009
DOI: 10.1021/jp906672u
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Adsorption at Single Crystal and Thin-Film Gold Electrodes: An In Situ Infrared Spectroscopy Study

Abstract: Adenine adsorption at gold electrodes is studied in neutral sodium fluoride solutions by cyclic voltammetry and in situ infrared spectroscopy. External reflection measurements were performed with Au(111) and Au(100) single crystal electrodes in D2O solutions, whereas surface enhanced infrared reflection absorption spectroscopy experiments under attenuated total reflection conditions were carried out with sputtered gold thin-film electrodes, both in D2O and H2O solutions. The results clearly show the specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 77 publications
3
39
0
Order By: Relevance
“…On the other hand, it is also known that DNA bases (nucleobases) can be adsorbed on some metal solid surfaces, particularly, on Au electrodes [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is also known that DNA bases (nucleobases) can be adsorbed on some metal solid surfaces, particularly, on Au electrodes [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous in situ FT-IRRAS studies of adenine adsorption on gold electrodes in neutral and in acid media [3,4] showed that only the neutral form of adenine (AdH 3 ) is chemisorbed on the electrode under these conditions, even at pH values as low as pH . Recent in situ electrochemical STM experiments also suggest the weak adsorption of the protonated adenine [5].…”
Section: -Introductionmentioning
confidence: 99%
“…On the other hand, the comparison of adenine adsorption in acid and in neutral media also reveals differences in the spectral signals corresponding to the solvent and to the anion of the supporting electrolyte [3,4], that indicate that the co-adsorption of these species with adenine takes place only in acid media.…”
Section: -Introductionmentioning
confidence: 99%
See 2 more Smart Citations